2008
DOI: 10.2478/v10079-008-0012-4
|View full text |Cite
|
Sign up to set email alerts
|

Survivin in cancer diagnosis and therapy - a review

Abstract: Survivin in cancer diagnosis and therapya reviewFailure of cancer treatment mainly results from metastasis formation and to a certain extent from local neoplastic infiltration. Numerous genes coding for growth factors and their receptors, adhesion proteins, and cell cycle regulatory proteins are involved in the process of carcinogenesis. Cancer microenvironment is characterized by uncontrolled production of growth factors and cytokines. In tumor specimens, an increased synthesis of the epidermal growth factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Survivin expression has prognostic significance in many types of human cancer (26). Small studies in human osteosarcoma have suggested that survivin may be useful in determining prognosis and degree of malignancy (27)(28)(29); however, definitive studies about the role of survivin in human osteosarcoma are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Survivin expression has prognostic significance in many types of human cancer (26). Small studies in human osteosarcoma have suggested that survivin may be useful in determining prognosis and degree of malignancy (27)(28)(29); however, definitive studies about the role of survivin in human osteosarcoma are lacking.…”
Section: Introductionmentioning
confidence: 99%